BRIDES FOR SALE: CROSS‐BORDER MARRIAGES AND FEMALE IMMIGRATION. (19th October 2016) - Kawaguchi, Daiji; Lee, Soohyung
Abstract : Developed East Asian countries import a large number of women from abroad as brides every year, although such cross‐border marriages virtually did not exist 20 years ago. With a theoretical framework and empirical evidence, we argue that developed Asian countries' demand for foreign brides is the consequence of improvement in women's economic status and gender‐discriminative household arrangements that insufficiently incorporate women's improved status in marriage. We offer sets of empirical evidence in line with our argument, using various macro‐ and microlevel datasets. ( JEL A12, J12, J61)